1990
DOI: 10.1002/j.2050-0416.1990.tb01047.x
|View full text |Cite
|
Sign up to set email alerts
|

Small Scale Mashing Experiments With Grists Containing High Proportions of Raw Sorghum

Abstract: Small scale mashes (BO g total grist) with grists containing high proportions of raw sorghum (50%-80% malt replacement) showed high values of extract recovery and produced worts of lower total nitrogen, free amino nitrogen, viscosity and colour but higher values of pH compared to worts produced from all malt mashes. Increasing the proportion of raw sorghum in the grist relative to malt resulted in a decline in extract recovery, wort total nitrogen, free amino nitrogen and an increase in wort pH.Addition of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 6 publications
4
30
0
Order By: Relevance
“…Equally essential are optimising conditions for mashing and fermentations of worts on the brewery pilot scale to achieve the desired goal of brewing buckwheat beer comparable to that from barley. The mashing problems encountered from brewing with buckwheat may be resolved by the use of novel combinations of industrial visco-enzyme preparations 12 . The wort filtration problem encountered may be resolved by using a mash filter instead of the lauter tun 1 or rice husks 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Equally essential are optimising conditions for mashing and fermentations of worts on the brewery pilot scale to achieve the desired goal of brewing buckwheat beer comparable to that from barley. The mashing problems encountered from brewing with buckwheat may be resolved by the use of novel combinations of industrial visco-enzyme preparations 12 . The wort filtration problem encountered may be resolved by using a mash filter instead of the lauter tun 1 or rice husks 52 .…”
Section: Discussionmentioning
confidence: 99%
“…More recent comprehensive reviews on brewing lager beer from sorghum, particularly, malted sorghum have been compiled by Agu and Palmer 2 and Owuama 38 . Due to problems associated with malted sorghum such as the development of insufficient diastatic power, limited protein modification, high malting costs, high malting losses, together with the need to supplement mashes with exogenous enzymes, it could seem more feasible to mash with unmalted grains and commercial enzymes 3,4,8,14,21,22,30,31 .…”
Section: -2863(9'8-32mentioning
confidence: 99%
“…Aisien and Muts 5 reported major problems when filtering beer made from 100% malted sorghum. Dale et al 14 however filtered sorghum beer without difficulty. In these trials, problems were not experienced when filtering the sorghum brews.…”
Section: +Viir Fiiv Jmpxvexmsrmentioning
confidence: 99%
“…Among the enzyme preparations used in this study, it was observed (Fig. 1a) that α-amylase was the principal enzyme of starch liquefaction during mashing 1,7,12 . Figures 1b, 1c and 1d show that the actions of β-amylase, filtrase and protease on starch liquefaction were only noticeable in the presence of α-amylase.…”
Section: Resultsmentioning
confidence: 87%
“…The addition of enzymes to increase fermentable sugars and free amino acids, and to facilitate filtration when mashing with poorly malted or unmalted cereals, is an established practice in beer brewing 1,2,6,7,10,12,15 . One of the most important technological parameters to which brewers pay attention during mashing is the ease with which the mash filters 8,10,17,19,20 .…”
Section: Introductionmentioning
confidence: 99%